PENGARUH KARAKTERISTIK PERUSAHAAN DAN PROFITABILITAS TERHADAP KELENGKAPAN PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018) - Futry Dwi Jayanti; Sylvia Christina Daat; Hastutie Noor Andrianti (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
This study aims to provide empirical evidence about the effect of company size, listing age, capital adequacy ratio, non-performing loans and profitability on voluntary disclosure. This study uses the independent variable size of the company, age of listing, capital adequacy ratio (CAR), non-performing loan (NPL) and profitability and the dependent variable is voluntary disclosure. The sample used in this study is the annual report of banking companies registered in 2015-2018 on the Indonesia Stock Exchange. Select 30 banking companies with purposive sampling. Data collection techniques are documentation, book reviews and literature. And the data analysis technique is multiple linear regression, which consists of descriptive statistical analysis, classic assumption test: normality, multicollinearity, autocorrelation, heteroscedasticity, and hypothesis testing. The results of the analysis show that all independent variables have a simultaneous significant influence on the level of completeness of voluntary disclosure. Then, company size, listing age significantly affect the level of completeness of voluntary disclosure. Conversely, the capital adequacy ratio (CAR), non-performing loan (NPL) and profitability do not have a significant effect on the level of completeness of voluntary disclosure.